Reclamation of process water from renewable source of Palm Oil Mill Effluent (POME) Using efficient hybrid membrane system - Jami, Mohammed Saedi; Muyibi, Suleyman Aremu; Idris Oseni, Munirat (2012)
This study evaluates the performance of ultrafiltration (UF) membrane system in the treatment of biologically treated palm oil mill effluent (POME) coupled with the use of coagulants as pretreatment to reduce turbidity that is associated with the effluent. Series of batch coagulation and flocculation processes with ferric chloride and aluminum sulphate under different conditions, i.e. dosage and pH were conducted in order to determine their optimum conditions. Polyacrylamide was used as coagulant aid and its optimum dose was also determined. The effects of transmembrane pressure and molecular weight cut-off (MWCO) were investigated. Flat sheet polyethersulfone (PES) ultrafiltration membrane of molecular weight cut-off (MWCO) 1, 5 and 10 kDa were used. The result of the coagulation process showed that ferric chloride gave a better reduction of turbidity at dosage of 100 mg/L, pH of 8 and with polyacrylamide (coagulant aid) dose of 100 mg/L than alum. Transmembrane pressure was varied between 0.5 to 1.5 bar and the performance of these membrane systems were assessed in terms of reduction of chemical oxygen demand (COD), color and turbidity in POME. Pretreatment played significant role in reducing COD, colour and turbidity by 97.9 %, 99.3 % and 99.9 %, respectively. The highest reduction of COD, colour and turbidity occurred at transmembrane pressure of 0.5 bar and better permeate quality was obtained with MWCO of 1 kD. The results also showed that UF membrane of MWCO of 5 kDa gave higher flux compared with MWCO of 1kDa.